2017
DOI: 10.1111/nin.12226
|View full text |Cite
|
Sign up to set email alerts
|

Social dimensions of health across the life course: Narratives of Arab immigrant women ageing in Canada

Abstract: The increase in ethnically and linguistically diverse older adults in Canada necessitates attention to their experiences and needs for healthy ageing. Arab immigrant women often report challenges in maintaining health, but little is known about their ageing experiences. This interpretive descriptive study uses a transnational life course framework to understand Arab Muslim immigrant women's experiences of engaging in health-promoting practices as they age in Canada. Women's stories highlight social dimensions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 40 publications
2
22
0
Order By: Relevance
“…Consistent with previous studies, this study revealed a positive association between perceived social support and the subjective well-being of ME migrants, especially their life satisfaction (Brajša-Žganec et al, 2018;Liu et al, 2017;Salma et al, 2018). Middle Eastern migrants' perceptions of their family, friends, and significant others as being supportive and reliable helpers in the way that suits their needs could give them a sense of stability and predictability in their life situations and makes them feel cared for, valued, esteemed, and connected to a group of people, resulting in their higher level of subjective well-being (Liu et al, 2017;Shishehgar et al, 2015).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Consistent with previous studies, this study revealed a positive association between perceived social support and the subjective well-being of ME migrants, especially their life satisfaction (Brajša-Žganec et al, 2018;Liu et al, 2017;Salma et al, 2018). Middle Eastern migrants' perceptions of their family, friends, and significant others as being supportive and reliable helpers in the way that suits their needs could give them a sense of stability and predictability in their life situations and makes them feel cared for, valued, esteemed, and connected to a group of people, resulting in their higher level of subjective well-being (Liu et al, 2017;Shishehgar et al, 2015).…”
Section: Discussionsupporting
confidence: 91%
“…In migrants, social support can be an important contributor to well-being, as migration is a major life event which invariably involves changes in socioeconomic status (SES), lifestyle, and environment (Brajša-Žganec et al, 2018). Lack of social support has been identified as a major post-migration barrier for ME migrants, due to the complexity and severity of challenges they face before and after migration (Salma et al, 2018;Shishehgar et al, 2015). However, there remains a dearth of knowledge regarding the factors associated with social support for ME migrants, making it difficult to identify the main areas of action to help ME migrants be part of a supportive social network, which could contribute to their subjective well-being (Shishehgar et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In the context of health, it would also be worthwhile to have more developed measures of transnational health services' use, including informal sources of medical advice and support. Qualitative studies have suggested that family and social networks may be sources of medical information and traditional medicines and therapies, particularly for managing chronic illness and during pregnancy and the postpartum period [83][84][85]. Overall, more work is needed to further develop and validate tools for measuring transnationalism specifically for health research.…”
Section: Discussionmentioning
confidence: 99%
“…Arab migrants have a greater prevalence of cardiovascular disease, cancers, diabetes, and other chronic conditions (Abdelmessih, Simpson, Cox, & Guisard, 2019; Zayed, Chebli, Shalabi, Taha, & Abboud, 2020). Despite the high proportion of Arab migrants and high prevalence of chronic disease, Arab people frequently do not access health services when symptoms appear or for ongoing care (Alhomaizi et al, 2018; Salma, Keating, Ogilvie, & Hunter, 2018). It is postulated that one reason for this is associated with the mismatch between the existing services and the needs of Arab people (Abdelmessih et al, 2019; Alananzeh, Levesque, Kwok, & Everett, 2016).…”
Section: Introductionmentioning
confidence: 99%